Liquid Glass: A Facile Soft Replication Method for Structuring Glass. Issue 23 (9th April 2016) - Kotz, Frederik; Plewa, Klaus; Bauer, Werner; Schneider, Norbert; Keller, Nico; Nargang, Tobias; Helmer, Dorothea; Sachsenheimer, Kai; Schäfer, Michael; Worgull, Matthias; Greiner, Christian; Richter, Christiane; et al.
Abstract : Liquid glass is a photocurable amorphous silica nanocomposite that can be structured using soft replication molds and turned into glass via thermal debinding and sintering. Simple polymer bonding techniques allow the fabrication of complex microsystems in glass like microfluidic chips. Liquid glass is a step toward prototyping of glass microstructures at low cost without requiring cleanroom facilities or hazardous chemicals.